SPECIFIC ACCOUNTING POLICIES ON PUBLIC INSTITUTIONS RELATED TO PROVISIONS, CONTIGENT LIABILITIES AND CONTIGENT ASSETS - Ţenovici Cristina Otilia (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2013)
Nowadays, the activity performed by professional accountants should be transparent and the communication process should be an efficient one so that the data transmitted is relevant and reliable. Such characteristics can become achievable only within a quality accounting referential, based on international accounting standards likely to integrate the public field particularities. The need to obtain comparable and transparent information in the public sector has determined the emergence of IPSAS standards, high quality standards with benefice consequences upon the world economy. The purpose of the disclose study is to analyse the development of accountancy in Romania and the level of accounting harmonization and convergence with IPSAS 19 “Provisions, contingent liabilities and contingent assets”. We are also focusing on performing a comparison between the main characteristics of the disclose national and international regulations, with the mention of resemblances and differences on provisions, contingent liabilities and contingent assets in order to identify the range of convergent and divergent issues.